Ethics in Learning: A Preferred Reporting Items for Systematic Reviews and Meta-Analyses - Endah Susilowati; Diah Hari Suryaningrum; Sari Andayani; Wulandari Hidayanti; Dana Puspitasari; Brian Bayu Ramadhan; St. Rohmawatik; Zakharia Vito Trinova (Nusantara Science and Technology Proceedings, 2022)
Researchers have used a systematic literature review to map the existing research, find existing knowledge of any field, and its gaps, and finally suggest possible future research. However, few studies assessing the nature and quality of systematic review papers published in the ethics and learning literature have been conducted. In this study, we use a list of Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) to systematically review the systematic review article on ethics in learning. We used data from crossref and google scholars indexed journals in the last decade from 2013 to 2022. We employed the terms “ethics, learning, and review” to obtain the ethics in learning review articles. The results of this study will provide researchers on how the review literature procedures have been conducted. This study not only will enhance our understanding of the procedures followed by scholars in doing systematic reviews, but also illustrate some limitations in the design, method, and implementation of current systematic reviews.